Conducting channel at the LaAlO3/SrTiO3 interface - COEY, JOHN; VENKATESAN, MUNUSWAMY (My University, 2013)
Localization of electrons in the two-dimensional electron gas at the LaAlO3/SrTiO3 interface is investigated by varying the channel thickness in order to establish the nature of the conducting channel. Layers of SrTiO3 were grown on NdGaO3 (110) substrates and capped with LaAlO3. When the SrTiO3 thickness is ≤6 unit cells, most electrons at the interface are localized, but when the number of SrTiO3 layers is 8–16, the free carrier density approaches 3.3×1014 cm−2, the value corresponding to charge transfer of 0.5 electrons per unit cell at the interface. The number of delocalized electrons decreases again when the SrTiO3 thickness is ≥20 unit cells. The ∼4 nm conducting channel is therefore located significantly below the interface. The results are explained in terms of Anderson localization and the position of the mobility edge with respect to the Fermi level.
PUBLISHED
Keywords: Physics